Interfacial phenomena in thin polymer films studied by direct profiling techniques - Budkowski, Andrzej (Kovine zlitine tehnologije, 1997)
Various interfacial phenomena, such as: phase coexistence, sufrace seggregation and wetting, as well as surface directed phase separation, determine many properties of polymer mixtures. These phenomena are studied in blands confined in a thin film geometry. Direct composition vs. depth profiling techniques are used, which have been developed in the last decade. Present paper describes briefly direct profiling methods and interfacial phenomena observed with their help. Discussion is illustrated by experimental results obtained for homopolymer mixtures with nuclear reaction analysis and secondary ion mass spectroscopy.
Keywords: polimeri; polimerne mešanice; tanke plasti; fazne meje; površinske lastnosti